The morphology of myeloma cells changes with the progression of the disease - Wajs, Jarosław; Sawicki, Waldemar (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : Multiple myeloma is a heterogeneous entity with variable course. Plasma cells found in bone marrow smears are characterised by extremely high diversity of morphology. We have attempted to determine whether the morphological characteristics of myeloma cells vary with the natural course of the disease. We investigated the incidence of selected morphological features and planimetric parameters of myeloma cells present in bone marrow smears. Material and methods : Material collected from 103 patients was evaluated at diagnosis and then during relapse. It was found that in the same patients, plasma cell morphology changes in the course of the disease: cell surface, nucleus surface, tumour cell anisocytosis and nuclear-cytoplasmic ratio increase significantly. Results : The results suggest that some morphological features are more common in clinically advanced disease. These include the number of nucleoli, the number of myeloma cells with irregular nuclei, and larger nuclei. Using the classification systems according to Greipp and Goasguen, we have noted changes in morphological pattern of myeloma cells in some patients with progressive multiple myeloma. This was associated with the appearance of a cell clone characterised by a set of traits indicating a low degree of maturity. Conclusions : We did not find that the type and intensity of cytostatic therapy significantly affect the morphology of plasma cells. Therefore, we suggest that some changes are due to natural, expansive course of the disease.